(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article attempts to study the specifics of the tunable paradigm simulation of O. Chupa’s novel «Cherry and I» in the aspect of presence production. Based on the concept represented in the work of the German-American literary critic, philosopher, historian H. U. Gumbrechtю Тhe author pointed out that any clash of man and culture, which creates a situation of aesthetic alertness, allows you to feel the elements as meaning (interpretation) so and presence (experience). Characters master the reality by comprehending its objectivity, involving both consciousness and body. The article deals with the leading modes of being embodied in the story of O. Chupa «Cherry and I», which are components of bodily-mimetic discourse within the framework of the presence effect as an attempt to «penetrate through material reality in an effort to master the spiritual truth», in order to better understand the truth about a person, his relationship with the world.